St. Theodore Studites (759-826) and His Apologetical Approach in the Antirretics (Defense of the Icons) - Penkov, Dimo (Forum Theologicum Sardicense, 2025)
Dimo Penkov, St. Theodore Studites (759-826) and His Apologetical Approach in the Antirretics (Defense of the Icons). The author analyzes the apologetic rhetorical elements in the three discourses against those who deny the worship of the holy icons. St. Theodore the Studite unfolds his refutations that develop even more the arguments of St. John Damascene and build upon it. The Saint sets forth the basic Christological dimensions of the arguments of the Orthodox defenders of the holy icons.